"What is a European hospital but a pagan shrine?" Missionaries, progress, and the problem of materiality in colonial Uganda. (3rd July 2018) - Bruner, Jason
ABSTRACT: Western missionaries frequently stood at the forefront of altering African systems of healthcare and belief. Medical missionaries often spoke of their work as a means of combatting "superstition" and re-orienting African concepts of disease and illness towards Western notions of causality and treatment. Amidst missionary panegyrics, however, were a range of perceptions of and reactions to missionary medicine from Christian and non-Christian Africans alike. This essay explores these processes of resistance and appropriation through a combined analysis of missionary medicine and missionary involvement with the Uganda Museum. No single group in colonial Uganda offered as trenchant a critique of missionary healthcare and their involvement with the museum as did the leaders of an independent church known as the Malakites. The Malakites contended that it was the missionaries themselves who were hindering true progress away from paganism. For them, all "pagan shrines, " whether of African or European origin, were an affront to the sovereign God, who needed no form of human intervention to heal.